The Role of Quarter Life Crisis and Transformational Leadership in Turnover Intention Among Generation Z in Bandung City - Dali Ramadhan; Puteri Andika Sari (Universitas Indonesia Membangun (Inaba), 2026)
Turnover intention The impact of Generation Z employees is an increasingly pressing issue in human resource management, as this generation tends to leave organizations more easily than previous generations. This study aims to describe quarter life crisis, transformational leadership, And turnover intention, and analyze partial and simultaneous influences quarter life crisis And transformational leadership to turnover intention on Generation Z in Bandung City. The study used a quantitative approach with a descriptive-verification method through a survey of 310 Generation Z respondents (born 1997-2007) in Bandung City who had worked at least once, selected through purposive sampling. Data were analyzed using multiple linear regression with IBM SPSS Statistics. The results showed that all three variables were in the high category. Quarter life crisis has a positive and significant effect on turnover intention (t = 15.921; sig. = 0.001), while transformational leadership has a negative and significant effect (t = -10.264; sig. = 0.001). Simultaneously, both variables have a significant effect on turnover intention (F = 219.461; sign. = 0.001) and explains 58.6% of the variation. This finding indicates that turnover intention in Generation Z is influenced by the interaction between internal psychological pressure and the quality of leadership support received, particularly the mentoring dimension of transformational leadership, which was found to be the weakest indicator among all the variables measured.